2022
DOI: 10.1136/bmjopen-2021-052630
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum high-sensitivity C reactive protein with risk of mortality in an Asian population: the Health Examinees cohort

Abstract: ObjectivesThis study aimed to examine the association of high-sensitivity C reactive protein (hsCRP) with mortality risk and the attenuated effect of non-communicable disease history (NCDhistory) on the association.DesignProspective cohort study.SettingHealth Examinees cohort.ParticipantsA total of 41 070 men and 81 011 women aged ≥40 years were involved (follow-up: 6.8 years).Outcome measuresData and cause of death occurring until 31 December 2015 were confirmed by death statistics from the National Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Participants who did not experience the event were censored on December 31, 2020. We selected confounders based on predictors of mortality that have been published in previous studies [ 30 , 33 ], and by evaluating multivariable Cox regression models. To examine the association of total UPF intake or UPF items/subgroups with all-cause or cause-specific mortality, sex-stratified hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox proportional hazard models with follow-up time as a time-scale variable.…”
Section: Methodsmentioning
confidence: 99%
“…Participants who did not experience the event were censored on December 31, 2020. We selected confounders based on predictors of mortality that have been published in previous studies [ 30 , 33 ], and by evaluating multivariable Cox regression models. To examine the association of total UPF intake or UPF items/subgroups with all-cause or cause-specific mortality, sex-stratified hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox proportional hazard models with follow-up time as a time-scale variable.…”
Section: Methodsmentioning
confidence: 99%
“…This increase was evident with a HR of 1.45 (95% CI, 1.05–2.01) in quartile 2 (0.70–1.39 mg/day), rising to 1.95 (95% CI, 1.42–2.69) in quartile 4 (3.02–10.0 mg/day) when compared to quartile 1 (0.09–0.70 mg/L) 18 . In a study conducted in Korea with a total of 41,070 men and 81,011 women aged 40 years or older (follow‐up duration: 6.8 years), it was found that there was a dose–response relationship between elevated hsCRP levels and the risk of all‐cause mortality in both genders 20 . This study included 2206 participants who were 80 years of age or older (with a median age of 93.0 years) from the Healthy Aging and Biomarkers Cohort Study (follow‐up: 3.1 years).…”
Section: Discussionmentioning
confidence: 99%
“…18 In a study conducted in Korea with a total of 41,070 men and 81,011 women aged 40 years or older (follow-up duration: 6.8 years), it was found that there was a dose-response relationship between elevated hsCRP levels and the risk of all-cause mortality in both genders. 20 Abbreviations: CI, confidence interval; HR, hazard ratio; hsCRP, high-sensitivity c-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations